The organization of repair in Yoruba conversation - Femi Akindele (LibraryPress@UF, 1991)
In any conversational event, co-participants are guided by rules which ensure a smooth conversation. According to Sacks et al. [1974:700] some of these rules are that "one party speaks at a time" and also that "speakerchange recurs, or at least occurs." Quite often these rules are broken as was found in Schegloff et al. [1977] for American English conversation and confirmed by Moerman [1977] for Thai conversation. I argue, therefore, in this paper following Schegloff et al. [1977:381] that if conversation is composed of systems of rules which are integrated, then it will have a source of "trouble" related to the modes of their integration. And if it has intrinsic sources of trouble, then it will have a mechanism for dealing with them intrinsically. I further argue that an adequate theory of the organisation of conversation in natural language in general, as proposed by Schegloff et al. [1977], and in Yoruba specifically, will need an account of the organisation of repair. I suggest that repair mechanisms in Yoruba will include those suggested by Schegloff et al. [1977] and supported by Moerman [1977], namely: self-repair which can issue from self-initiation or other initiation and other repair which arises from self-initiation or other initiation. I conclude that these repair mechanisms are indices of participants' orientation to the making of Yoruba conversational interaction.